Development Of Magnetorheological Elastomers Based On Natural Rubber And Industrial Waste Nickel Zinc Ferrite - Moksin, Nordalila (2019)
Magnetorheological elastomers (MREs) which consist of rubber and magnetic particles have attracted increasing attention in engineering applications and research due to its excellent dynamic performance. In this work, MREs based on industrial waste nickel zinc ferrite and natural rubber was produced. The dynamic properties were investigated using lost tangent, tan δ. Curing characteristics, thermal stability, morphology characteristics were also evaluated in this work. From SEM results, it was evident that isotropic MRE has uniform magnetic fillers dispersion in rubber matrix while anisotropic MRE had chain like structure of magnetic filler, however, the interface between nickel zinc ferrite and rubber matrix was poor. Tan δ for anisotropic MREs were found higher compared with isotropic MREs over the whole range of frequency and strain amplitude explored. The adhesion between nickel zinc ferrite with natural rubber matrix was then improved by using bis [3-(triehoxysilyl) propyl] tetrasulfide (TESPT) as the surface modification for magnetic particles with varied content at 2, 4, 6, 8, and 10 wt%. The result revealed that silane coupled improved the dynamic mechanical strength and tensile strength and the optimum content of TESPT was 6 wt%. Tan δ of developed MREs with addition of carbon black also were compared with conventional damping rubbers. The results revealed that tan δ was higher than comparative samples supporting the nickel zinc ferrite to improve dynamic properties.